Neoadjuvant chemotherapy for FIGO stage III or IV ovarian cancer: Survival benefit and prognostic factors. Issue 5 (1st August 2003) - Shibata, K.; Kikkawa, F.; Mika, M.; Suzuki, Y.; Kajiyama, H.; Ino, K.; Mizutani, S.
Abstract : The survival benefit of neoadjuvant chemotherapy (NAC) was assessed in patients with FIGO stage III or IV ovarian cancer, and the prognostic value of various therapeutic factors was determined. In patients treated for stage III or IV ovarian malignancies at the Department of Obstetrics and Gynecology of Nagoya University or related institutions between 1987 and 1996, 119 had a histologic diagnosis of serous cystadenocarcinoma. For this group, the long-term outcome was compared between 96 patients receiving conventional adjuvant chemotherapy following standard surgery and 23 patients treated with NAC, both followed by a second cytoreductive surgery. In a total of 29 patients with all histologic types of malignancy, the tumor response to NAC and survival were analyzed on the basis of histology, chemotherapy regimen, residual tumor size after the second cytoreductive operation, and the dose intensity of cisplatin. The long-term outcome (5-year survival rate) was better in patients treated with conventional adjuvant chemotherapy than in patients receiving NAC, although the difference was not significant. Overall survival did not differ significantly in relation to tumor histology or chemotherapy regimen. With respect to residual tumor size after the second surgery, patients with a residual tumor ≦ 2 cm in diameter had a significantly better prognosis than those with a residual tumor >2 cm. A better prognosis was also associated with a higher dose intensity of cisplatin, and patients treated at ≧ 18 mg/m 2 /week survived significantly longer than those receiving <18 mg/m 2 /week.